2011
DOI: 10.1093/restud/rdr022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the City Size Wage Gap

Abstract: In this paper, we decompose city size wage premia into various components. We base these decompositions on an estimated on-the-job search model that incorporates latent ability, search frictions, firm-worker match quality, human capital accumulation and endogenous migration between large, medium and small cities. Counterfactual simulations of the model indicate that variation in returns to experience and differences in wage intercepts across location type are the most important mechanisms contributing to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(164 citation statements)
references
References 30 publications
7
154
2
1
Order By: Relevance
“…Several studies have concluded that the urban -rural wage gap is partly or completely due to differences in wage growth between urban and rural areas (Glaeser and Mare, 2001;Wheeler, 2006;Yankow, 2006;Gould, 2007;Baum-Snow and Pavan, 2012;Wang, 2013;De la Roca and Puga, 2014). Wage growth seems to have a substantial between-job component (Wheeler, 2006;Yankow, 2006), and workers at least partly keep wage gains when moving to other regions, indicating that returns to work experience in urban areas are portable (D'Costa and Overman, 2014;De la Roca and Puga, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that the urban -rural wage gap is partly or completely due to differences in wage growth between urban and rural areas (Glaeser and Mare, 2001;Wheeler, 2006;Yankow, 2006;Gould, 2007;Baum-Snow and Pavan, 2012;Wang, 2013;De la Roca and Puga, 2014). Wage growth seems to have a substantial between-job component (Wheeler, 2006;Yankow, 2006), and workers at least partly keep wage gains when moving to other regions, indicating that returns to work experience in urban areas are portable (D'Costa and Overman, 2014;De la Roca and Puga, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A similar assumption is found in Baum-Snow & Pavan (2012). In terms of the model, a sufficient condition for ruling out the possibility of migration into unemployment is that the difference in lifetime 26 See the discussion in the online appendix of Cahuc, Postel-Vinay & Robin (2006).…”
Section: Assumption 3 Job-related Migration -Jobseekers Cannot Migratmentioning
confidence: 72%
“…One way to overcome this issue is to consider a very stylized definition of space. This is the path taken by Baum-Snow & Pavan (2012), who consider a model which includes several appealing features such as individual ability and location-specific human capital accumulation, but have to resort to a ternary partition of space between small, midsized and large cities.…”
Section: Migrationmentioning
confidence: 99%
“…This is counterfactual. Using individual data, Wheeler (2001) and Baum-Snow and Pavan (2012) estimate that the skill premium and the returns to experience of US workers increase with city size. 62 A theoretical framework that delivers a positive relationship between city size and the returns to productivity is provided in Davis and Dingel (2013) and Behrens and Robert-Nicoud (2014b).…”
Section: Agglomeration and Urban Inequalitymentioning
confidence: 99%